Dual Effects of Neuroprotection and Neurotoxicity by General Anesthetics on Neural Stem Cells: Role of Autophagy - Wang Yan; Wang Xiu; Wei Huafeng (Journal of Evolving Stem Cell Research, 2017)
General anesthetics (GAs) are widely used for various essential surgical or medical procedures. Recent studies implicate the GAs has dual effects of neuroprotection and neurotoxicity on neurogenesis with unclear mechanisms. This minireview summarizes recent studies on GAs mediated effects on neurogenesis and proposed mechanisms, with focus on autophagy regulation and intracellular calcium homeostasis.
Keywords: General anesthetics